Maximizing Teacher Competence and Performance: The Influential Factors Across Individuals, Organizations, Leadership, and Environment – A Comprehensive Systematic Review and Model - Erna Yayuk; Yudha Alfian Haqqi (STAI Hubbulwathan Duri, 2024)
This research is constructed in a systematic literature review that identifies and maps the factors influencing teacher competence and performance. The competence and performance of teachers relate to the success of the teaching strategy applied to develop the knowledge and personality of students. Therefore, educational institutions or interested parties must determine the factors influencing teacher competence and performance for evaluation material in establishing sustainable development, education, and teacher training programs. This research aims to (1) identify individual factors that affect teacher competence, (2) identify organizational factors that affect teacher competence, (3) identify leadership factors that affect teacher competence, (4) identify environmental factors that affect teacher competence, (5) identify individual factors that affect teacher performance, (6) identify organizational factors that affect teacher performance, (7) identify factors leadership that affects teacher performance, and (8) identify environmental factors that affect teacher performance. The sample in this study included 45 identified articles from 463 articles taken by purposive sampling through journal indexing portals in the form of Google Scholar, IEEE, and Scopus. Data collection techniques used PICOS and a Systematic Review Diagram based on PRISMA with data analysis in the form of mapping using the Systematic Review model. The results show a significant influence of individual, organizational, leadership, and environmental factors on teacher competency and performance. Therefore, it is necessary to make efforts for educational institutions to maximize teacher competence and performance after knowing the dominant driving factors that arise so that educational institutions can provide competency and performance improvement facilities for teachers.